Dynamic changes in physical function during intensive chemotherapy affect transplant outcomes in older adults with AML - Min, Gi-June; Cho, Byung-Sik; Kwag, Daehun; Park, Sung-Soo; Park, Silvia; Yoon, Jae-Ho; Lee, Sung-Eun; Eom, Ki-Seong; Kim, Yoo-Jin; Lee, Seok; Min, Chang-Ki; Cho, Seok-Goo; et al. (Frontiers in Oncology, 2023)
Intensive chemotherapy (IC) can affect all geriatric assessment (GA) domains in older adults with acute myeloid leukemia (AML), but data on the effects of these changes on transplant outcomes are lacking. We prospectively assessed the prognostic role of GA domains at diagnosis and allogeneic hematopoietic stem cell transplantation (allo-HSCT) in 51 patients with AML aged ≥60 years who achieved complete remission after IC. We performed both baseline and pre-allo-HSCT GA; moreover, physical function, including a short physical performance battery (SPPB), cognitive function, psychological function, nutritional status, and social support were examined. All GA domains showed dynamic changes between the two time points. The directions of change were statistically significant for social support, self-reported physical and psychological functions, and distress, but not for nutritional status, cognitive function, or objectively measured physical function. Among all GA domains at each time point, only poor physical function and its submaneuvers at diagnosis but not at allo-HSCT were significantly associated with inferior survival. In particular, since the direction of change varied between patients, we found that patients whose physical function improved before allo-HSCT were more likely to survive longer than those with persistently impaired SPPB (55.6% vs. 28.6%, p=0.268). Finally, persistent impairment in SPPB (28.6% vs. 65.9%, p=0.006), tandem stand (0% vs. 63.3%, p=0.012), sit-and-stand (41.2% vs. 70.6%, p=0.009), and gait speed (38.5% vs. 68.4%, p=0.027) further strongly predicted inferior survival. This study showed that IC courses can induce dynamic changes in different directions in the GA domains of each patient and that changes in objectively measured physical function can predict transplant outcomes.